Anatomic versus reverse shoulder arthroplasty: a mid-term follow-up comparison. (October 2021) - Schoch, Bradley S; King, Joseph J; Zuckerman, Joseph; Wright, Thomas W; Roche, Chris; Flurin, Pierre-Henri
Background: Anatomic total shoulder arthroplasty improves pain and function with a reported reoperation rate of approximately 1% per year. With improved glenoid fixation, reverse shoulder arthroplasty implants may outperform anatomic total shoulder arthroplasty. We evaluate the functional outcomes and reoperation rate of anatomic total shoulder arthroplasty versus reverse shoulder arthroplasty at a minimum eight-year follow-up or revision. Methods: Between 2005 and 2010, 187 shoulders (137 anatomic total shoulder arthroplasty, 50 reverse shoulder arthroplasty) were retrospectively reviewed at a mean of 8.8 years. The mean age at surgery was 67 years. Females were more commonly treated with reverse shoulder arthroplasty. Both groups had similar body mass index and comorbidities. Outcome measures evaluated included abduction, forward elevation, external rotation, internal rotation, Simple Shoulder Test, Constant score, American Shoulder and Elbow Score, University of California Los Angeles Shoulder score, and Shoulder Pain and Disability Index. Results: At follow-up, anatomic total shoulder arthroplasty demonstrated greater overhead range of motion and external rotation. All patient-reported outcomes remained similar between groups. Reverse shoulder arthroplasty patients were more likely to rate shoulders as much better or better after surgery (90% versus 67%, p = 0.004). Complications were observed in 24% of anatomic total shoulder arthroplasties and 8% of reverse shoulder arthroplasties (p = 0.02). Reoperation was more common in anatomic total shoulder arthroplasties (23% versus 4%, p = 0.003). Discussion: At mid-to-long-term follow-up, reverse shoulder arthroplasties demonstrated significantly fewer complications and reoperations than anatomic total shoulder arthroplasties. Despite similar patient-reported outcomes, reverse shoulder arthroplasty patients were more likely to be satisfied with their shoulder.